(untitled) (African Journal of Law and Politics, 2025)
Despite the significant contribution of protected areas in halting the degradation of natural resources and conserving biodiversity in Central Africa‚ the proliferation of this mechanism, is also being questioned by local communities who feel threatened with the dispossession of their lands by governments in complicity with conservators and non-governmental organizations (NGOs). Protected areas have stirred up conflicts‚ with social and economic impacts that affect catchment communities who rely on forest resources found within these areas‚ who have seen their livelihood opportunities eroded. This article closely examines the implications of creating protected areas on the rights of local communities in Cameroon‚ with a particular focus on the Tofala Hill Wildlife Sanctuary (THWS) in the Wabane and Alou Sub-Division‚ in the South West Region of Cameroon. The article holds that rather than promote communal land rights and participation in natural resource management‚ protected areas for and conservation has strengthened state’s supremacy over local communities in the management of natural resource.